Principales problemas de la juventud rural colombiana y políticas públicas vinculadas - German Darío Hémbuz Falla; Beatriz Del Carmen Peralta Duque (Eleuthera)
This article is a research product that addresses the problems of rural youth in Colombia and the related public policies, particularly those related to coffee youth. The general objective is to analyze the needs and potentialities of young farmers (aged between 14 and 28 years) in the department of Huila, Colombia. The methodology used is based on the epistemic foundation of articulated consciousness, proposed by Hugo Zemelman and the non-parametric didactics of Estela Quintar, with tools of Participatory Action Research in the construction of a territorial public agenda. In the results, the experiences of young subjects who study and work in the field are revealed, and they are profiled as historical and autonomous subjects in the articulated reconstruction of possible utopias. Among the conclusions obtained, it is highlighted that the population of the municipalities under analysis has not been the object of public policies linked to the youth of the coffee-growing region.